CFD supported scale up of perfusion bioreactors in biopharma - Kuschel, Maike; Wutz, Johannes; Salli, Mustafa; Monteil, Dominique; Wucherpfennig, Thomas (Frontiers in Chemical Engineering, 2023)
The robust scale up of perfusion systems requires comparable conditions over all scales to ensure equivalent cell culture performance. As cells in continuous processes circulate outside the bioreactor, performance losses may arise if jet flow and stirring cause a direct connection between perfusion feed and return. Computational fluid dynamics can be used to identify such short circuit flows, assess mixing efficiencies, and eventually adapt the perfusion setup. This study investigates the scale up from a 2 L glass bioreactor to 100 L and 500 L disposable pilot scale systems. Highly resolved Lattice Boltzmann Large Eddy simulations were performed in single phase, and mixing efficiencies (Emix) furthermore experimentally validated in the 2 L system. This evaluation gives insight into the flow pattern, the mixing behavior and information on cell residence time inside the bioreactors. No geometric adaptations in the pilot scale systems were necessary since Emix was greater than 90 % for all conditions tested. Two different setups were tested in 2 L scale where the direction of flow was changed, yielding a difference in mixing efficiency of 10 %. Remarkably, the setup with the lower mixing efficiency resulted in conditions closer to pilot scale bioreactors, whereas the other setup showed a more robust mixing efficiency over various power inputs. Determined mixing times were in a similar range for all scales. The results demonstrate how computational fluid dynamic models can be used for rational process design of intensified production processes in the biopharmaceutical industry.